Emerging prospects of microbial production of omega fatty acids: Recent updates. (September 2022) - Patel, Anil Kumar; Chauhan, Ajeet Singh; Kumar, Prashant; Michaud, Philippe; Gupta, Vijai Kumar; Chang, Jo-Shu; Chen, Chiu-Wen; Dong, Cheng-Di; Singhania, Reeta Rani
Graphical abstract: Highlights: Balanced ω-3:ω-6 fatty acid diet ratio (1:4) leads to good health management. Their imbalance ratio causes chronic inflammation, autoimmunity, obesity, etc. Large-scale microbial ω-FAs production is a prerequisite for their rising demands. Strategy to enhance microbial ω-6 could be promising for wellbeing and bioeconomy. Abstract: Healthy foods containing omega-3/omega-6 polyunsaturated fatty acids (PUFAs) have been in great demand because of their unique dietary and health properties. Reduction in chronic inflammatory and autoimmune diseases has shown their therapeutic and health-promoting effects when consumed under recommended ratio 1:1–1:4, however imbalanced ratios (>1:4, high omega-6) enhance these risks. The importance of omega-6 is apparent however microbial production favors larger production of omega-3. Current research focus is prerequisite to designing omega-6 production strategies for better application prospects, for which thraustochytrids could be promising due to higher lipid productivity. This review provides recent updates on essential fatty acids production from potential microbes and their application, especially major insights on omega research, also discussed the novel possible strategies to promote omega-3 and omega-6 accumulation via engineering and omics approaches. It covers strategies to block the conversion of omega-6 into omega-3 by enzyme inhibition, nanoparticle-mediated regulation and/or metabolic flux regulation, etc.